Pulmonary involvement in systemic lupus erythematosus. Issue 6 (December 1978) - Grennan, D M; Howie, A D; Moran, F; Buchanan, W W
Abstract : Several series have suggested that pulmonary function abnormalities are common in systemic lupus erythematosus. However, only isolated studies have attempted to relate these abnormalities to immunological aspects of the diseases. In the present study respiratory symptoms, pulmonary function tests, and immunological data were reviewed in 22 patients with systemic lupus erythematosus. Seventeen subjects had either clinical evidence or abnormalities of lung function suggestive of pulmonary involvement. A restrictive ventilatory defect or reduction in pulmonary diffusing capacity for carbon monoxide was demonstrated in 14 of the patients only 4 of whom were dyspnoeic. There was no correlation between pulmonary involvement, co-existent renal lupus, and immunological abnormality.